Synthesis and characterization of bimetallic gold-silver (Au-Ag) nanocatalyst via seed colloid technique / Nurafaliana Berahim - Nurafaliana, Berahim (2020)
In the present study, unique catalysts of monometallic gold (Au), silver (Ag) and bimetallic gold-silver (Au-Ag) nanoparticles (NPs) were prepared with different size or diameters by the citrate-thermal reduction and the seed colloidal techniques, respectively. The catalytic nanoparticles were characterized by various advanced analytical techniques such as Ultraviolet-visible spectroscopy (UV-vis), zeta potential, electron dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), High-angle annular dark-field (HAADF) scanning transmission-electron microscopy (STEM) imaging and the energy dispersive spectroscopy (EDS) elemental mapping. The catalytic performance of the nanoparticles were ascertained through the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) in the presence of sodium borohydride (NaBH4). The results of the study clearly showed that the rate of 4-NP reduction to 4-AP increased with a corresponding decrease in the size or diameter of the bimetallic NPs. The Au seed volume of 5.0 ml indicated relatively higher reduction rates as compared to that of 2.0 ml. However, the monometallic NPs showed relatively lesser catalytic activity in the reductive conversion of 4-NP to 4-AP. The catalytic properties of the bimetallic Au-Ag nanoparticles also reinforced with a direct impact of the size and composition of the bimetallic nanoparticles.